Extreme and rapid bursts of functional adaptations shape bite force in amniotes. Issue 1894 (9th January 2019) - Sakamoto, Manabu; Ruta, Marcello; Venditti, Chris
Abstract : Adaptation is the fundamental driver of functional and biomechanical evolution. Accordingly, the states of biomechanical traits (absolute or relative trait values) have long been used as proxies for adaptations in response to direct selection. However, ignoring evolutionary history, in particular ancestry, passage of time and the rate of evolution, can be misleading. Here, we apply a recently developed phylogenetic statistical approach using significant rate shifts to detect instances of exceptional rates of adaptive changes in bite force in a large group of terrestrial vertebrates, the amniotes. Our results show that bite force in amniotes evolved through multiple bursts of exceptional rates of adaptive changes, whereby whole groups—including Darwin's finches, maniraptoran dinosaurs (group of non-avian dinosaurs including birds), anthropoids and hominins (fossil and modern humans)—experienced significant rate increases compared to the background rate. However, in most parts of the amniote tree of life, we find no exceptional rate increases, indicating that coevolution with body size was primarily responsible for the patterns observed in bite force. Our approach represents a template for future studies in functional morphology and biomechanics, where exceptional rates of adaptive changes can be quantified and potentially linked to specific ecological factors underpinning major evolutionary radiations.